The appropriation of mindfulness in the Evangelical Lutheran Church of Finland - Marcus Moberg; Tommy Ramstedt (Approaching Religion, 2023)
Mindfulness has gained increasing popularity across Western societies over the past couple of decades, although mainly in forms that have been stripped of all religious content. During this period, the practice has also attracted the interest of mainstream Christian churches, which has precipitated the development of distinctively ‘Christian’ forms of mindfulness. Based on a critical discussion of the concept of appropriation in the sphere of religion, this article explores the particular logic whereby mindfulness has been appropriated within the particular ecclesiastical context of the Evangelical Lutheran Church of Finland (ELCF) in light of debates in church-connected media and the content of two Finnish BA theses on pastoral care that argue for the adoption of the practice. In light of this data, the article illustrates how ELCF discourse on mindfulness has been marked by four closely interlinked requirements for the appropriation of the practice: 1. that the practice has already been thoroughly stripped of any overt religious content; 2. that it has become sufficiently scientifically validated; 3. that there is wider social and cultural interest in the practice; 4. and that the practice does not stand in opposition to the teachings of the church.